2016
DOI: 10.3390/w9010011
|View full text |Cite
|
Sign up to set email alerts
|

Fouling Communities of Two Accidental Artificial Reefs (Modern Shipwrecks) in Cyprus (Levantine Sea)

Abstract: Abstract:Artificial reefs are considered one of the alternative methods in fisheries management, used in order to enhance stocks and marine biodiversity in general. A number of biotic and abiotic parameters influence the fouling communities' formation on artificial reefs through complex interactions. In order to understand how epibiotic or fouling communities progress through time, it is important to study these communities in mature artificial reefs, especially those that have been around for many decades, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In contrast, on Zenobia, the sites sampled where more sheltered (darker) due to the positioning of the wreck, hence limiting the dominance of algal species. Based on findings published elsewhere [ 19 ], two other modern shipwrecks in Cyprus, Touba and Cricket, showed similar percentage of algae (~15%) as the Zenobia. A detailed description of the algae species in both wrecks most probably will further clarify the trends found in the present study.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In contrast, on Zenobia, the sites sampled where more sheltered (darker) due to the positioning of the wreck, hence limiting the dominance of algal species. Based on findings published elsewhere [ 19 ], two other modern shipwrecks in Cyprus, Touba and Cricket, showed similar percentage of algae (~15%) as the Zenobia. A detailed description of the algae species in both wrecks most probably will further clarify the trends found in the present study.…”
Section: Discussionmentioning
confidence: 79%
“…Currents are expected to greatly impact fouling communities as they interfere with larval settlement and food supply as well as sedimentation [ 33 ], hence able to facilitate faster growth. Sites directly exposed to currents are more diverse compared to communities exposed to moderate currents [ 19 ]. It has been also suggested that vertical sites of artificial reefs exposed to direct current, support greater diversity than horizontal surfaces [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first deployments of ARs strongly aimed to increase the associated ichthyofauna for the improvement of commercial fishing [3,4]. However, during the last decade, the studies of ARs have shifted towards a more integrated ecosystem approach (e.g., [5,6]), in order to understand the communities colonizing the ARs, and how to use the gained knowledge for habitat "rehabilitation" and "restoration" [4,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%